Methodology of applying standard costing and normative methods in manufacturing enterprises - Tamulevičienė, Daiva; Mackevičius, Jonas; Gaižauskas, Lionius (Buhalterinės apskaitos teorija ir praktika, 2020)
Appropriate choice of the production cost calculation methods helps not only to estimate the production cost correctly, but also to correctly determine prices of products as well as their profit and profitability, draw up budgets, control expenses, make operational and prospective management decisions. The article analyses effective standard costing and normative methods that are still seldom applied in Lithuanian enterprises. A brief history of how the methods were created is provided. The advantages and aims as well as their similarities and differences are analysed. A methodology of applying standard costing and normative methods in manufacturing enterprises was prepared. Application of these methodologies is going to help managers and accountants to introduce the methods easier and at a lower cost.